Teletrabalho na pandemia: serviço público que não tem hora para acabar - Machado, Priscila Silva Ximenes (2022)
This research aims to understand how telework established during the pandemic carried out in Minas Gerais Federal Justice. More specifically, we intended to analyze the impact of teleworking during the pandemic on the public servant's journey; the distribution of responsibility for the costs involved with teleworking; the peculiarities inherent to working in a virtual environment and, finally, the impact of teleworking on family and social relationships during the pandemic. For that purpose, a field research was carried out through semi-structured interviews with teleworkers and managers of the Federal Regional Court of the 6th Region (Minas Gerais state). The present research concluded that telework contributes to unpaid overwork, teleworker hyperconnection and the expansion of the working day. We observed the loss of labor collective dimension, low social interaction and worker isolation.